Particle simulation of the strong magnetic field effect on dust particle charging process - Hadi Davari; Bizhan Farokhi; Mohammad Ali Asgarian (Scientific Reports, 2023)
Abstract A particle-in-cell simulation is modeled and run on a dusty plasma to determine the effect of the magnetic field on the process of dust-particle charging through electron–ion plasma. The electric field is solved through the Poisson equation, and the electron-neutral elastic scattering, excitation, and ionization processes are modeled through Monte Carlo collision method. The effects observed from the initial density of the plasma, the initial temperature of the electrons, and the changing magnetic field are included in this simulation model. In the dust particle charging process, saturation time and saturation charge are compared. An increase in the magnetic field does not reduce time to reach the saturation state. Determining the magnetic field boundaries which depend on the physical properties of the plasma, can be contributive in some areas of dusty(complex) plasma. The applications of the results obtained here for fusion plasma conditions and space and laboratory plasmas are discussed. The results here can be applied in future simulation models with a focus on the dust particle movement and their effect on plasma, leading to the modeling of different astrophysical plasmas thorough laboratory experiments.